Diagnosing Primary Malignancy in Leptomeningeal Carcinomatosis by Using CSF Cytology and Immunohistochemistry: A Case Report - Hasthavaram, Navaneeth Reddy; Dadu, Tina; Duggal, Rajan; Qureshi, Suhail; Baghmar, Saphalta; Agarwal, Amit; Khurana, Aseem; Sarin, Aditya; Singh, Navdeep; Kumar, Ramesh (Indian Journal of Medical and Paediatric Oncology, 2020)
We present a rare case of recurrent carcinoma of gallbladder with leptomeningeal carcinomatosis. Cerebrospinal fluid (CSF) cytology showed atypical cells, which were suspicious for malignancy on initial reporting. Diagnosis of malignancy and primary from hepatobiliary source was confirmed by doing immunohistochemistry on CSF cell block.
Keywords: Gallbladder carcinoma; immunohistochemistry; leptomeningeal